2010
DOI: 10.1016/j.pain.2010.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of medication overuse in patients with migraine

Abstract: This multi-center study compared the therapeutic effect of a cognitive-behavioral minimal contact program (MCT) to the effect of a brochure (bibliotherapy) for the prevention of medication overuse headache (MOH) in migraine patients. Seven German headache centers recruited 182 migraine patients with high triptan or analgesic intake frequency. Patients were randomly allocated to either the MCT-group, receiving both an MCT program and an educational brochure or to the biblio-group receiving only the brochure. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
1
64
0
7
Order By: Relevance
“…In the field of headaches, it has been showed that subjects with chronic daily headaches exhibit increased catastrophizing scores when compared to episodic migraineurs, higher catastrophizing being associated with lower quality of life [15]. Moreover the prevention of MOH in high frequency migraine patients by a cognitive behavioural program is associated with a lowering of catastrophizing [16]. …”
Section: Discussionmentioning
confidence: 99%
“…In the field of headaches, it has been showed that subjects with chronic daily headaches exhibit increased catastrophizing scores when compared to episodic migraineurs, higher catastrophizing being associated with lower quality of life [15]. Moreover the prevention of MOH in high frequency migraine patients by a cognitive behavioural program is associated with a lowering of catastrophizing [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies support the idea that frequent intake of antimigraine drugs is caused not only by the intensity of headache pain and frequency of the attacks, but also by fear and loss of social function, observations highlighting the importance that psychology can have on intake behavior [2]. Comorbidity of anxiety and depression frequently exists in patients with chronic daily headache [2].…”
Section: Introductionmentioning
confidence: 98%
“…For example, in Denmark main topics are imparted by headache nurses whereas in Germany predominantly doctors and psychologists conduct patient education sessions. In an outpatient setting with a focus on education, written information (bibliotherapy) might be as useful as cognitive-behavioral group sessions that could be shown in a randomized clinical trial with patients at risk for MOH (27).…”
Section: Disadvantage Of Approachmentioning
confidence: 99%